2018
DOI: 10.3892/etm.2018.6570
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective effect of lactoferrin in mice exposed to sublethal X‑ray irradiation

Abstract: The radioprotective effect of lactoferrin (LF) was studied in mice subjected to sublethal X-ray irradiation. The mice were randomly divided into the Control (non-irradiated mice fed a standard diet without LF), IR (irradiated mice fed a standard diet) and IR+LF (irradiated mice fed LF) groups. The mice were fed daily for 7 days prior to irradiation and for 30 continuous days following irradiation. The survival ratio of the mice in the IR+LF group was significantly increased compared with the IR group between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…This protein is involved in many physiological functions, including regulation of iron absorption and immune responses. It demonstrates antibacterial, antiviral, anti-inflammation, anticarcinogenic, antioxidant, and radioprotective activities [ 21 , 22 , 23 , 24 ]. Neurons of PD patients have been found to accumulate high concentrations of Lf [ 25 ]; on the other hand, the number of Lf receptors is increased in dopaminergic neurons resistant to the disease process [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This protein is involved in many physiological functions, including regulation of iron absorption and immune responses. It demonstrates antibacterial, antiviral, anti-inflammation, anticarcinogenic, antioxidant, and radioprotective activities [ 21 , 22 , 23 , 24 ]. Neurons of PD patients have been found to accumulate high concentrations of Lf [ 25 ]; on the other hand, the number of Lf receptors is increased in dopaminergic neurons resistant to the disease process [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the mice weights in both Lf treatment irradiated groups were restored to the level of the corresponding control on days 15 (IR+Lfx2) and 18 (IR+Lf), respectively. It has been previously reported that the body weights of the mice decreased between day 8 and 10 after X-ray irradiation at 7.0 Gy [4]. Between days 20 and 30, the body weight was significantly higher in the animals received a diet containing bovine Lf.…”
Section: Resultsmentioning
confidence: 86%
“…The significant difference was identified between the IR and IR+Lf groups (p = 0.030). It has been previously established that Lf stimulated hematopoiesis [11] and recovery of leukocytes [4] in mice following irradiation.…”
Section: Table 1 Body Weights (G) Of Irradiated Mice At Different Time Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Lf can exert its antioxidant activity by direct iron chelation or by regulating key antioxidant enzymes directly involved in reactive oxygen species (ROS) scavenging [64]. Moreover, recent studies have highlighted the ability of Lf to prevent DNA double-strand breaks, both in cell models challenged with aflatoxins [65] and in mice irradiated with sub-lethal X-rays [66].…”
Section: Discussionmentioning
confidence: 99%